Mortality, temperature, and public health provision: A comment on Cohen and Dechezlepretre (2022) - Grant Benjamin; Ben Couillard; Jonathan D. Hall (Institute for Replication (I4R), 2023)
Cohen and Dechezleprêtre (2022) investigate the heterogeneous impact of temperature on mortality across Mexico, and how affordable healthcare services that target the low-income population attenuate the mortality effects of weather events. They find that while extreme temperatures are more dangerous than less extreme temperatures, the increased frequency of non-extreme temperatures mean these temperatures cause more deaths. First, we reproduce the paper's main findings, uncovering a minor coding error that has a trivial effect on the main results. Second, we test the robustness of the results to clustering at the state level, omitting precipitation, and using a different weighting scheme. The original results are robust to all of these changes.
Keywords: I12; I13; I14; O13; O14; Q54; 330; Mortality; Weather Events; Affordable Health Care; Poverty